Analysis of Consumer Satisfaction on Product Instant Ginger Herbal Drink in The Ex-Residence of Surakarta - Choirul Anam; Risdhania Salsabila; Windi Atmaka; Danar Praseptiangga; Achmad Ridwan Ariyantoro; Anastriyani Yulviatun (Universitas Sebelas Maret (UNS), 2024)
Ginger is a herbal plant that is quite popular. It has a distinctively spicy taste, so it can provide warmth to the body, and it is widely used as a cooking spice, medicine, and herbal drink. Ginger contains essential oils with active chemical compounds, such as: zingiberene, camphor, lemonin, borneol, shogaol, cineol, fellandren, zingiberol, gingerol, and zingerone. Consumer satisfaction is the performance achievement of a product or service that consumers receive in accordance with consumer expectations. The urgency of this research is to determine the quality properties of ginger-based product“Polanmadu Instant Ginger Herbal Drink” that meet consumer criteria, the priority of improving product attributes, and the level of consumer satisfaction with the product. The basic method used in this research is the descriptive method utilizing Google Forms-based questionnaires. The size of respondents was determined using the Slovin formula, with a total of 100 respondents. The data analysis consisted of descriptive analysis, customer satisfaction index, and importance performance analysis using Microsoft Excel 2013 and SPSS version 25 software. This study's results indicate that most respondents were satisfied with Polanmadu Instant Ginger Herbal Drink with a product performance index value of 80.42%. Product attributes that have met consumer satisfaction were price, practicality, aroma, and shelf life. Meanwhile, attributes that have a high priority for improvement are aftertaste, ease of obtaining, packaging size, packaging design, and product information.